Business Ethics as a Science Methodology and Implications - Storchevoy, Maxim (Springer International Publishing, 2018)
The book considers how to make the methodology of business ethics more scientific, especially its normative branch. Storchevoy explores the attempts of economic theory to contribute to the scientific normative analysis of economic behavior, particularly the welfare economics of 1910-1950 and methodological discussions of economics and ethics from 1980-2015. He then examines the development of the methodological structure of business ethics in general since the 1980s and the scientific validity of normative business ethics, including stakeholder theory, the separation thesis, integral social contract theory, corporate social responsibility, virtue ethics and other frameworks. He concludes by suggesting an additional step to make business ethics a more systematic discipline by developing a typology of moral issues and dilemmas. Business Ethics as a Science will be a thought-provoking resource for students and practitioners of business ethics and economists alike.